Indonesia’s Border Security and Political Nationalism Means in Dealing with Nationalism Problem at Indonesia-Malaysia Border Area (2009-2014) - Adityo Darmawan Sudagung (International Journal of Environment, Architecture, and Societies, 2021)
This paper aimed to examine Indonesia's means in 2009-2014 to deal with Indonesian nationalism problem at West Kalimantan-Sarawak border. The means of it divided into two categories: securing the border and political nationalism. The disparity between Indonesian and Malaysian at West Borneo-Sarawak border became the cause of societal security problem. National identity problem showed with the rising problem of Indonesian people nationalism at the research site. The research method used in this paper was a qualitative method with a descriptive case study technic. Data collection did by interview and documentation study. Securing the border means was done by guarding the border area and state frontier. Added by the diplomacy toward Malaysia in border issues. Political nationalism means was done firstly by showing state attention and existence. This means was done by doing physical development and delivering aid. Secondly, by giving education and empowerment to the people. Indonesia has done some means to deal with nationalism problem. However, there were still some obstacles, such as coordination and communication problem, human resources quality, and the lack of commitment.